Therapeutic Nutrition in Type 2 Diabetes Management: An Evidence-Based Review - Abdulkreem, Ghenaa H.; Ahmed, Noor Sarhan; Al-Hamdani, M. T. (American Journal of Botany and Bioengineering, 2026)
Type 2 diabetes mellitus (T2DM) is a long-term metabolic disorder characterised by persistently high blood glucose levels arising from a combination of an inability to register blood glucose levels and insufficient insulin production. The prevalence of T2DM has continually increased over the past few decades, around the world, causing a need for appropriate and sustainable methods to manage type 2 diabetes mellitus. One key aspect of the management of type 2 diabetes mellitus is nutritional therapy, as it plays the main role in regulating glucose levels, regulating body weight, and preventing diabetes complications. This review focuses on dietary strategies and the effects of macronutrient ratios, functional foods, and micronutrients on the metabolic outcomes of individuals with diabetes. Also included are reviews of a few modern dietary approaches that may positively affect blood sugar management, including low glycemic index, Mediterranean-style diets, and vegetarian/vegan diets. Additionally, there is a discussion of how bioactive compounds and gut microbes contribute to overall metabolic regulation. New advances in personalized nutrition and digital health technologies have provided more ways to help people implement effective dietary interventions; however, barriers such as adherence to new methods, economic status, and traditional eating patterns, make it difficult to implement these interventions successfully. The results of this review suggest that successful long-term management of type 2 diabetes will require individualized evidence-based nutrition interventions that are combined with modifications to the lifestyle of each individual.